Restructuring the Mixed Economy of Welfare: Three Modes of Privatization. (March 2015) - Gilbert, Neil
Abstract : Since the early‐1990s arrangements for social protection in most of the advanced industrialized nations have undergone a series of policy reforms that are restructuring the mixed economy of modern welfare states. This paper reviews several fundamental reasons for these changes and their substantive character, focusing on the increasing role of the private sector in the finance and delivery of welfare state activity. Three basic modes to increase private responsibility for heretofore publicly financed and publicly delivered social provisions are identified, illustrating alternative paths which advance the movement toward privatization. The assumptions and implications associated with these modes of privatization are analyzed.